Dissimilation of Aromatic Compounds by Alcaligenes eutrophus - Johnson, B. F. (1971)
The range of aromatic compounds that support the growth of Alcaligenes eutrophus has been determined, and the pathways used for the dissimilation of these substrates have been explored, largely by enzymatic analyses. The β-ketoadipate pathway operates in the dissimilation of benzoate and p-hydroxybenzoate; the genetisate pathway, in the dissimilation of m-hydroxybenzoate; and the meta cleavage pathway, in the dissimilation of phenol and p-cresol. l-Tryptophan is oxidized via anthranilate; but the metabolic fate of anthranilate was not established. The metabolism of the three stereoisomers of muconic acid was also examined.